Toward a psychophysiology of performance: sport psychology principles dealing with anxiety - Davis, P. A.; Sime, W. E. (International Journal of Stress Management, 2005)
In this applied case study during an off-season period, a unique and innovative internal imagery/video/electroencephalogram (EEG) biofeedback protocol was used to train visual attention and increase self-confidence of a collegiate baseball player struggling to recover from a serious eye injury. Results from the ensuing competitive season revealed that self-confidence increased and hitting and fielding performance improved dramatically. In the subsequent competitive season, without psychological skill training, hitting and fielding performance declined to preintervention levels. Although EEG biofeedback has been slow to gain acceptance among applied practitioners, used in conjunction with video and internal imagery, it appears to have potential as a tool for training visual attention in athletes within a variety of externally paced sports, such as baseball, softball, and racquet sports.